2017
DOI: 10.1016/j.bbamem.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative molecular dynamics study of neuromyelitis optica-immunoglobulin G binding to aquaporin-4 extracellular domains

Abstract: Neuromyelitis optica (NMO) is an inflammatory demyelinating disease of the central nervous system in which most patients have serum autoantibodies (called NMO-IgG) that bind to astrocyte water channel aquaporin-4 (AQP4). A potential therapeutic strategy in NMO is to block the interaction of NMO-IgG with AQP4. Building on recent observation that some single-point and compound mutations of the AQP4 extracellular loop C prevent NMO-IgG binding, we carried out comparative Molecular Dynamics (MD) investigations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…A total of 313 PSGs ( Tables S14 and S15 ) were found in the Yangtze finless porpoise lineage. Our analysis revealed that several PSGs are associated with osmotic adjustment, including aquaporin 4 ( AQP4 ), cystic fibrosis transmembrane conductance regulator ( CFTR ), and guanylate cyclase activator 2B ( GUCA2B ) [ 40 , 41 , 42 ]. AQP4 encodes a member of the aquaporin family of intrinsic membrane proteins, which regulates body water balance.…”
Section: Materials and Methods Results And Discussionmentioning
confidence: 99%
“…A total of 313 PSGs ( Tables S14 and S15 ) were found in the Yangtze finless porpoise lineage. Our analysis revealed that several PSGs are associated with osmotic adjustment, including aquaporin 4 ( AQP4 ), cystic fibrosis transmembrane conductance regulator ( CFTR ), and guanylate cyclase activator 2B ( GUCA2B ) [ 40 , 41 , 42 ]. AQP4 encodes a member of the aquaporin family of intrinsic membrane proteins, which regulates body water balance.…”
Section: Materials and Methods Results And Discussionmentioning
confidence: 99%
“…All MD simulations were performed using NAMD 2.10 ( Phillips et al, 2005 ) and the CHARMM36 force field ( Best et al, 2012 ). The full system was minimized and in order to remove steric clashes in the initial geometry, we applied a minimization and equilibration protocol consisting of four phases and reported in recent co-authored papers ( Alberga et al, 2014 ; Alberga et al, 2017 ): i ) minimization (2,500 steps) applying harmonic restraints (force constant k = 1 kcal mol −1 Å −2 ) on the protein atoms; 2 ) equilibration at T = 310 K with protein atoms kept at fixed positions for 200 ps; 3) relaxing at T = 310 K for 200 ps by applying harmonic restraints only to the protein atoms (force constant k = 1 kcal mol −1 Å −2 ); 4) gradual heating from T = 10–310 K, increasing the temperature of 25 K every 40 ps. The SHAKE algorithm was employed to constrain all R–H bonds ( Kräutler et al, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the rapid development of nanoscience and nanotechnology, advanced computational methods could be valuable tools for biomolecular interaction description and comprehension as well as they can extensively contribute to the understanding of MOG as a target during the demyelination process 15 . The application of computational techniques of modelling and simulation in the demyelinating disease research is in the beginning, but showed promising results in the description and characterisation of autoantigens, antigen presenting process, and T-cell activation 16,17 .…”
Section: Introductionmentioning
confidence: 99%